2016
DOI: 10.1073/pnas.1518260113
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response regulates yeast small GTPase Arl1p activation at late Golgi via phosphorylation of Arf GEF Syt1p

Abstract: ADP ribosylation factor (Arf) GTPases are key regulators of membrane traffic at the Golgi complex. In yeast, Arf guanine nucleotide-exchange factor (GEF) Syt1p activates Arf-like protein Arl1p, which was accompanied by accumulation of golgin Imh1p at late Golgi, but whether and how this function of Syt1p is regulated remains unclear. Here, we report that the inositol-requiring kinase 1 (Ire1p)-mediated unfolded protein response (UPR) modulated Arl1p activation at late Golgi. Arl1p activation was dependent on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…In some settings, the Golgi quality control contributes to UPR by capturing misfolded proteins that emanate from the ER, diverting them for lysosomal degradation (36). In fact, it is known that cleaved ATF6 induces ERGIC53 expression (37) and its redistribution so that it is closer to the cis-Golgi (38), both of which are features present in cells expressing Ala92-D2 HY .…”
Section: Introductionmentioning
confidence: 99%
“…In some settings, the Golgi quality control contributes to UPR by capturing misfolded proteins that emanate from the ER, diverting them for lysosomal degradation (36). In fact, it is known that cleaved ATF6 induces ERGIC53 expression (37) and its redistribution so that it is closer to the cis-Golgi (38), both of which are features present in cells expressing Ala92-D2 HY .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that Ire1−Hac1 signaling regulates Arl1 activity by controlling Syt1 phosphorylation (Fig. 2) (Hsu et al, 2016). Ire1 is a kinase/endoribonuclease that localizes to the ER membrane and is activated by ER stress (Kimata and Kohno, 2011;Parmar and Schröder, 2012).…”
Section: Arf-gefs and Their Regulatorsmentioning
confidence: 97%
“…Genetic alterations of Arl1 as well as its effectors were used to characterize developmental and physiological phenotypes (summarized in Fig. 1) (Chang et al, 2015;Cruz-Garcia et al, 2013;Eiseler et al, 2016;Gehart et al, 2012;Hesse et al, 2013;Hsu et al, 2016;Labbaoui et al, 2017;Lieu et al, 2008;Liu et al, 2006;Lock et al, 2005;Marešová and Sychrová, 2010;Marešová et al, 2012;Murray and Stow, 2014;Price et al, 2005;Torres et al, 2014;Yang and Rosenwald, 2016). In mammalian cells, these functions affect a wide range of fundamental cellular processes, including cell polarity (Lock et al, 2005), innate immunity (Bremond et al, 2009;Lieu et al, 2008;Murray and Stow, 2014;Stanley et al, 2012), lipid droplet and chylomicron formation (Hesse et al, 2013;Jaschke et al, 2012), as well as the secretion of insulin (Gehart et al, 2012), chromogranin A (CruzGarcia et al, 2013) and matrix metalloproteinases (MMPs) (Eiseler et al, 2016).…”
Section: The Physiological Roles Of Arl1mentioning
confidence: 99%
See 2 more Smart Citations